ANALISIS DAN PERANCANGAN ALAT ASAP CAIR MENGUNAKAN SISTEM PENDINGIN KONDENSOR TIPE SPIRAL - Jainal Arifin; Firda Herlina; Rendi Rendi (Universitas Lambung Mangkurat, 2022)
Liquid smoke consists of phenolic compounds, carbonyl compounds, acids, water, tar compounds, and benzopyrene. Natural wood material consisting of hemicellulose, cellulose, and lignin decomposes at high temperatures into more than 300 compounds consisting of more than 70 types of carbonyls as ketones and aldehydes, 20 types of acids, 11 types of furans, 45 types of phenols, 13 types of alcohols and esters. , 12 types of polycyclic aromatic carbon, and 13 types of lactones. The research method is by designing tools, and cutting/making liquid smoke tools, then drying them in the sun to be completely dry, Weighing the coconut material before putting it into combustion, assembling and connecting the house pipe hose from the reactor to the tar to the condenser pipe, making sure there are no the leak between the connections, before being put in the combustion furnace, turn on the fire in the reactor tube, install the condenser pipe in the condenser tube and fill the water in the condenser tube, record the results of liquid smoke every 8 hours and fill the material into the combustion tube. From the results of the research that has been carried out, there are differences in the results of liquid smoke obtained, then the charcoal results obtained, there is a difference in weight produced between the previous tool and the tool that is now designed, the most influencing factor is the condenser design, where the condenser can cool the smoke that comes out , due to the long cooling cycle that affects the results. The results obtained on the previous tool were 3.754 ml of liquid smoke, 6.5 kg of residual charcoal, and liquid smoke yield of 12.5% ​​with a burning time of 48 hours, and the production rate of liquid smoke was 78.2 ml/hour. The results of the research obtained on the new tool produced 7.095 ml of liquid smoke, 5.6 kg of residual charcoal, and 23.6% yield of liquid smoke with a burning time of 48 hours, and the production rate of liquid smoke was 147.8 ml/hour.